1999
DOI: 10.1111/j.1472-8206.1999.tb00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of aminoguanidine

Abstract: It is well known that aminoguanidine (AG) can diminish advanced glycosylation of proteins, which might be beneficial in preventing chronic diabetic complications. Recent reports suggested an inter-relationship between glycosylation of protein and free radical damage. In the present study, we examined the free radical scavenging properties of AG. Electron paramagnetic resonance using the spin-trap 5,5-dimethyl-1-pyrroline N-oxide (DMPO) was performed to determine the superoxide and hydroxyl radical scavenging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 24 publications
2
34
0
2
Order By: Relevance
“…AG has been reported to be an effective hydroxyl radical scavenger. 37 AG exhibits a significant dose-dependent effect against free radical damage. Aminoguanidine has been shown to exhibit trapping activity toward lipid-derived aldehydes such as MDA and 4-hydroxynonenal.…”
Section: Discussionmentioning
confidence: 99%
“…AG has been reported to be an effective hydroxyl radical scavenger. 37 AG exhibits a significant dose-dependent effect against free radical damage. Aminoguanidine has been shown to exhibit trapping activity toward lipid-derived aldehydes such as MDA and 4-hydroxynonenal.…”
Section: Discussionmentioning
confidence: 99%
“…According to the methods of Courderot-Masuyer et al ( 14 ), the reaction mixture containing 37.5 n M allophycocyanin, 3 m M AAPH, and aqueous solution of test sample in 75 m M phosphate buffer (pH 7.0) was incubated at 37˚C. The fluorescence obtained just before the addition of the radical generator AAPH was used as the 100% value for that sample.…”
Section: Methodsmentioning
confidence: 99%
“…10 In addition to being an inhibitor of NOS, aminoguanidine also exhibits antioxidant activity. [11][12][13] It was reported that induction of iNOS after I/R increased peroxynitrite formation, has harmful effects on various tissues.…”
Section: Introductionmentioning
confidence: 99%